COMPETENCIES OF PUBLIC HEALTH CARE PROFESSIONALS AND COMPETENCY DEVELOPMENT NEEDS IN PROVIDING QUALITY SERVICES TO ADOLESCENTS - Anužienė, Birutė; Norkienė, Sigutė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This article presents findings of the study of public health care professionals' attitude toward the specific competencies in adolescent health care and competency development needs. The study is based on the assumption that adolescents are specific receivers of services provided by public health care professionals; the services, therefore, should be provided with due regard to age, developmental, interpersonal, community, organisational, structural, and other intrinsic factors in terms of adolescents. When counselling adolescents, public health care professionals should be proficient in the following domains: communication style, consultation structure, policies and procedures, involvement of parents/guardians in an adolescent health care process, etc. Proficiency in the above domains requires specific competencies in adolescent health care. An analysis of public health care professionals’ attitude, in view of their existing competencies in adolescent health care, might help to respond more comprehensively the following problematic questions: Why are adolescents to be considered unique clients of services provided by public health care professionals? What do competencies in adolescent health care consist of? What are the needs for competencies of public health care professionals in adolescent health care and development thereof? Thus, this article is aimed to reflect an attitude of public health care professionals toward the specific competencies in adolescent health care and competency development needs. The article consists of an introduction and two parts: the first part provides theoretical assumptions; the second part is dedicated to an empirical analysis of an attitude of public health care professionals toward the specific competencies in adolescent health care, a content thereof, and competency development needs in view of existing competencies in adolescent health care. The article ends with a discussion and conclusions, followed by references.